Finite-time trajectory tracking control for a 12-rotor unmanned aerial vehicle with input saturation. (October 2018) - Fu, Chunyang; Tian, Yantao; Huang, Haiyang; Zhang, Lei; Peng, Cheng
Abstract: Finite-time trajectory tracking problem for a novel 12-rotor unmanned aerial vehicle (UAV) with input saturation is investigated in this paper. The UAV is divided into outer loop (altitude system and translational system) and inner loop (attitude system), and hierarchical structure is adopted to design the control scheme. In order to ensure finite-time convergence property and compensate input saturation impact simultaneously, a finite-time backstepping control strategy combined with a finite-time auxiliary system is proposed for the outer loop. Additional signals are generated to prevent control performance degradation caused by input saturation. The finite-time stability for outer loop is rigorously proved via Lyapunov theory. For inner loop, linear active disturbance rejection control is employed for attitude controllers design to enhance the robustness against the lumped disturbances. Finally simulation experiments illustrate the effectiveness and superiority of the proposed algorithm. Highlights: The outer loop of the 12-rotor UAV gains finite-time convergence tracking performance. The outer loop of the 12-rotor UAV acquires faster convergence rate, higher precision control performance and stronger disturbance rejection property. The outer loop of the 12-rotor UAV compensates the effect of thrust input saturation. The inner loop of the 12-rotor UAV achieves good control performance and strong robustness to lay a good foundation for the finite-time trajectory tracking task.